Mandibular reconstruction using a calcium phosphate/polyethylene glycol hydrogel carrier with BMP‐2. (13th June 2014) - Gruber, Rudolf M.; Krohn, Sebastian; Mauth, Corinna; Dard, Michel; Molenberg, Aart; Lange, Katharina; Perske, Christina; Schliephake, Henning
Abstract Aim To test the hypothesis that a synthetic hydroxyapatite/β‐tricalcium phosphate (HA/TCP) construct combined with polyethylene glycol (PEG) hydrogel including recombinant human bone morphogenetic proteins‐2 (rhBMP‐2) enhances new bone formation compared with bone morphogenetic proteins‐2 (BMP‐2) delivered using the HA/TCP construct alone. Material and Methods Bilateral mandibular partial thickness 20 × 8 × 8 mm (L × W × H) alveolar defects were surgically created in the edentulated posterior mandible in 18 female minipigs. Randomized into two groups of nine animals each, the alveolar defects either received HA/TCP or HA/TCP/PEG with or without BMP‐2 (105 μg/defect) in contra‐lateral sites using a split‐mouth design. Primary outcome, bone density (%) within four regions of interest, was evaluated following a 4‐week healing interval when the animals were killed for histometric analysis. Results Bone morphogenetic proteins‐2 loaded onto HA/TCP constructs significantly enhanced new bone formation compared with HA/TCP controls. Adding PEG apparently obstructed BMP‐2 induced bone formation. Conclusion Polyethylene glycol compromises the osteogenic effect of BMP‐2.